Production uncertainty in the inland navigation market: climate change, optimal barge size, and infrastructure investments - Piet Rietveld; Erhan Demirel; Jos van Ommeren (European Regional Science Association (ERSA), 2011)
Low water levels are a potential threat to the inland navigation market. We develop a theoretical model to analyze low water-level uncertainty in the inland navigation market. A negative effect of climate change on welfare is expected due to the increase in cost per tonne of transport when low water levels occur more frequently. The market actors may take measures to adapt to the new situation of climate change. As an example, we study barge-size adjustments by barge operators. We show that in the current market (both before and after climate change) there are incentives to almost double the barge size. The reason that this still has not occurred may be explained by the long lifetime of barges that are currently in use. Thus, climate change does not provide a reason to stop the current trend towards larger barges. The only effect is that this trend towards larger barges will end at a lower size than would be the case without climate change. The public sector may also take measures to decrease the harm caused by climate change. In this study we consider an investment in infrastructure by means of dredging. We find a benefit-cost ratio higher than for this for investments both before and after climate change. Thus, both with and without climate change, welfare would increase if government intensifies dredging. After climate change, public adaptation may be more important than private adaptation when the situation is optimal before climate change. For the combined effect of barge-size adjustment and infrastructure investment, it can be concluded that the benefit in terms of expected welfare is 'super-additive' for the situation before climate and also for the situation after climate change when starting from the current situation. This 'super-additivity' property can be attributed to the opportunity for barge operators to hold even larger barges in the new environment where low water is less harmful for their capacities. However, for the situation after climate change, when starting from an optimized situation, super-additivity no longer holds.
Keywords: 330